1975
DOI: 10.1111/j.1744-7348.1975.tb01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf respiration in relation to growth and photosynthesis of Lolium

Abstract: Six Lolium genotypes with contrasting apparent photorespiration and CO, compensation concentration, [CO,],, were compared for net photosynthesis, dark respiration, leaf starch accumulation, rate of leaf expansion and shoot regrowth. Plants were grown in day/night temperatures of 15/10 and 25/20 "C. There were significant (P < 0'05) differences between the genotypes in all these parameters. At 25/20 "C apparent photorespiration was correlated with [COJ,. Correlation coefficients, pooled from both temperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
3

Year Published

1977
1977
2000
2000

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 20 publications
(25 reference statements)
0
39
3
Order By: Relevance
“…Trin., is intermediate between C3 and C4 plants with respect to photorespiration. In contrast to other reports in the literature of C3 species with altered rates of photorespiration (4,12,14,(21)(22)(23), this observation has been independently confirmed in several laboratories based on a variety of CO2 exchange parameters, including reductions in the 02 inhibition of net photosynthesis, the CO2 compensation concentration (F)2, and the rate of CO2 evolution in the light (2,3,8,10,12).Although leaf anatomical studies of P. milioides have revealed some features of Kranz anatomy characteristic of C4 plants (2, 3, 9), biochemical investigations (8)(9)(10)(11)13) indicate that this species has not reduced photorespiration and the associated 02 inhibition of photosynthesis by a C4-like CO2 concentrating mechanism (5). For example, the primary products of photosynthesis in 14CO2-air are 3-P-glycerate and glycerate rather than C4 dicarboxylic acids (8,9,11).…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…Trin., is intermediate between C3 and C4 plants with respect to photorespiration. In contrast to other reports in the literature of C3 species with altered rates of photorespiration (4,12,14,(21)(22)(23), this observation has been independently confirmed in several laboratories based on a variety of CO2 exchange parameters, including reductions in the 02 inhibition of net photosynthesis, the CO2 compensation concentration (F)2, and the rate of CO2 evolution in the light (2,3,8,10,12).Although leaf anatomical studies of P. milioides have revealed some features of Kranz anatomy characteristic of C4 plants (2, 3, 9), biochemical investigations (8)(9)(10)(11)13) indicate that this species has not reduced photorespiration and the associated 02 inhibition of photosynthesis by a C4-like CO2 concentrating mechanism (5). For example, the primary products of photosynthesis in 14CO2-air are 3-P-glycerate and glycerate rather than C4 dicarboxylic acids (8,9,11).…”
contrasting
confidence: 53%
“…Trin., is intermediate between C3 and C4 plants with respect to photorespiration. In contrast to other reports in the literature of C3 species with altered rates of photorespiration (4,12,14,(21)(22)(23), this observation has been independently confirmed in several laboratories based on a variety of CO2 exchange parameters, including reductions in the 02 inhibition of net photosynthesis, the CO2 compensation concentration (F)2, and the rate of CO2 evolution in the light (2,3,8,10,12).…”
contrasting
confidence: 49%
“…The use of the uncoupler of oxidative phosphorylation CCCP suggested that leaf respiration of the studied lines was controlled by adenylates in a similar It is generally considered that some reduction of total plant respiration would offer the possibility of a small, but significant, increase in yield (1,15,16). In this sense, several authors (1,11,15,16,28) suggested that selection of plants for lower mature leaf respiration per unit dry weight results in significantly higher yields. Bugbee and Salisbury (9) discussed the limits ofcrop potential productivity and suggested that carbon use efficiency, which is inversely related to respiration, can still be significantly increased in plants.…”
Section: Leaf Respiration In the Darkmentioning
confidence: 99%
“…WILSON (1975) found a CVg of21% for leaf dark respiration in perennial ryegrass and a CVg of 24% was measured by PENNING DE VRIES (pers. commun.)…”
Section: A Simple Model For Rg R Of Isolated Plantsmentioning
confidence: 99%